SAT0576 Improved clinical scenario for chikungunya diagnosis. (15th June 2017) - Rueda, JC; Angarita, J-I; Santos, AM; Saldarriaga, E-L; Pelaez-Ballestas, I; Soares-Santeugini, MJ; Londono, J
Abstract : Background: The World Health Organization (WHO) criteria for chikungunya virus infection (CHIKV) have a specificity of 91, 1% with a low sensibility of 56, 2%, which decreases the ability to detect patients with the infection. Because of this issue a group of rheumatology, epidemiology and bacteriology experts in diagnosing and treating CHIKV patients performed an agreement consensus on the clinical characteristics of CHIKV infection and proposed a set of clinical criteria. In order to test the performance of the new criteria and improve sensibility and specificity a clinical scenario was developed with the agreements from the expert panel and the clinical characteristics with higher odds ratios. Objectives: To improve sensibility and specificity of a set of clinical criteria for the diagnosis CHIKV. Methods: Odds ratios of the clinical features of patients with CHIKV infection were analysed. A clinical scenario was developed and sensitivity and specificity was calculated. Results: 37 clinical characteristics were evaluated in a cohort of 604 patients with suspicion of CHIKV. From those, 29 exhibited statistical significance and only 10 had high odds ratios (table 1 ). A clinical scenario with the following joint involvement (symmetrical arthritis of shoulders or wrists or hands or knees or ankles or feet) or systemic symptoms (fever or rash or myalgia or fatigue) poised a sensitivity of 74, 2% (PPV: 83, 5%) and a specificity of 88, 4% (NPV: 81, 2%). The following clinical characteristics extracted from the agreements of the consensus group were added to the clinical picture: origin from an epidemic area and abrupt onset of symptoms. Conclusions: Our study demonstrated that the proposed clinical scenario for suspicion of CHIKV improves diagnostic sensibility with a slight decrease in specificity, increasing the chance of diagnosis without the need for laboratory tests. We propose that a patient from an epidemic area (fulfilling epidemiological criteria according to the WHO) with an abrupt onset of a clinical picture of symmetrical arthritis of any of the following joints: hands, wrists, shoulders, knees or feet, or the presence of any of the following systemic symptoms: fever, rash, fatigue or myalgia, is more likely to have CHIKV infection. Disclosure of Interest: None declared